Penerapan Online Learning dengan Framework Cobit 5 Untuk Mendukung Program Merdeka Belajar Kampus Merdeka - Sri Restu Ningsih; Seri Hartati; Liza Trisnawati; Rosa Devitria (Yayasan Literasi Sains Indonesia, 2022)
The era of the Digital Revolution 4.0 needs to be addressed with appropriate learning so that students have superior competencies in the field of education. This must be responded quickly and accurately by all stakeholders in education in order to be able to increase the competitiveness of the Indonesian nation in the midst of increasingly competitive competition. The process of information technology management level through the Cobit 5 Framework shows that educational institutions in Riau Province are still in level 2, namely the managed process level. We need a solution to accelerate technology, especially online learning, which is a necessity in various educational institutions. SMAN 8 Pekanbaru has implemented online learning with the measured readiness of managed process technology. The model used is the seamless learning model which is a method that provides an effective learning environment, contains the concepts of continuity and continuity in the learning process that occurs without time and space limits. The purpose of this Community Service activity is to implement online learning at SMAN 8 Pekanbaru in the form of workshops for teachers in schools using the Cobit 5 Framework. The results of this activity show significant changes, especially in the enrichment of online learning learning models. The survey results from the satisfaction of teachers showed a score of 98% strongly agree with the benefits resulting from this community service activity.